BRADOU: um glossário de termos e sociotermos do Corpo de Bombeiros Militar do Maranhão - PEREIRA, José Claudio Bezerra (2020)
This research aimed to raise, describe and systematize the terminology of the Military Fire Department of Maranhão, hereinafter called CBMMA, used in the capital of São Luís/MA, for registration purposes in a glossary. Currently, CBMMA is located in 18 municipalities in the State, but only in the capital, performs activities in other specialized segments in addition to firefighting. This study is mainly justified by the emancipation of CBMMA occurred in 1993, since the main hypothesis of this investigation was based on the strong probability that this autonomy, because it made possible the dismemberment and specification of activities within this institution, would have generated a terminology within this corporation. Another reason that justifies the importance of the present work is that, according to the obtained so far, there is only one kind of glossary of technical terms of the Military Fire Department of Santa Catarina - CBMSC. In line with the foregoing, the main research issues on which this work were: a) what are the lexical items that, in fact, reflect the particularities of the labor relations developed within the CBMMA, that is, attest to the existence of a terminology within this corporation?; b) which lexical units are most frequent and/or specific in each of the specialised barracks?; c) members with longer service time use a specialized lexicon different from that used by those who have less time in the corporation?; d) there are consubstantial differences between the specialized lexicon used by men and women within CBMMA? In the case of answering these questions, the fundamentals were used, especially terminology and socioterminology developed by Sager (1990), Cabré (1993), Gaudin (1993), Faulstich (1995), Krieger e Finatto (2004) e Barros (2004). Methodologically, the corpus of this study was extracted from oral interviews conducted through the application of a questionnaire composed of closed and 01 open questions related to the daily work of professionals of both sexes, of 7 specialized units of the CBMMA: 1º BBM, BBA, BBMAR, BBEM, SCI, BBS e ABMJM. These informants were distributed in three ranges of service time: (i) service time 1 - TS1, from 2 to 10 years; (ii) service time 2 - TS2, from 15 to 25 years; and (iii) - service time 3 - TS3, more than 30 years. As a result, it was identified that terms as cried, which is the notification of any and all occurrences that had entered within the CBMMA. The present work has its relevance to the extent that the specialized lexicon of a given group has the ability to reflect and materialize the sociocultural heritage of this group. Added to this is the fact that the results achieved will serve as a basis for conducting further research on the terminology of the Fire Department in other brazilian states, which, consequently, will enhance the interaction between the members of different units of the Fire Department in Brazil.